2019
DOI: 10.1007/978-3-319-78030-6_35
|View full text |Cite
|
Sign up to set email alerts
|

Development of Functional Dairy Foods

Abstract: There has been a growing interest on functional foods, markedly recognized as being able to provide additional benefits on health promotion, wellbeing maintenance, and disease prevention. Based on this scenario, food industries have been increasingly focused in developing added-value foodstuffs, being dairy foods one of the most currently used food products for functional purposes. Different extraction and encapsulation technologies have been used to obtain target food bioactive ingredients and to ensure an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The use of by-products from the food industry as functional ingredients added in bakery products [68] Bakery products…”
Section: Biscuits and Breadsmentioning
confidence: 99%
“…The use of by-products from the food industry as functional ingredients added in bakery products [68] Bakery products…”
Section: Biscuits and Breadsmentioning
confidence: 99%
“…Foods rich in dietary fiber and antioxidants can satisfy some of the demands for health benefits (Sakač et al, 2011;Perez et al, 2018). Intake of dietary fiber and antioxidants has been related to the maintenance of health and/or reduction of the incidence of certain diseases (Lobo et al, 2010;Martins et al, 2019;Alasalvar et al, 2020). In the present study, the cookies prepared from 30% chia seeds composition showed high inhibition activity against free radical scavenger and highest inhibition activity was recorded in 52.06% at 500 ug/ml concentration (Table 3).…”
Section: Manufacturing Of Novel Bakery Products With Elevated Functio...mentioning
confidence: 50%
“…Processed meat products are generally added with chemical preservatives for increasing the shelf-life of meat products, but with recent disillusionment of consumers with chemical additives has piqued researchers and scholars to explore natural preservatives. Herbs, spices, plant extracts, and essential oils have been used for extending storage life of meat [3][4][5], dairy [6], and bakery products [7].…”
Section: Introductionmentioning
confidence: 99%